AMENDMENTS TO THE SPECIALIZED LAW ON VIRTUAL ASSETS: IMPLEMENTATION OF THE EUROPEAN MICA REGULATION - Hrytsai, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Aim: on February 17, 2022, the Parliament of Ukraine adopted the Law of Ukraine "On Virtual Assets" No. 2074-IX. The full launch of the Ukrainian virtual asset market was planned by lawmakers from 01.10.2022 simultaneously with the adoption of Draft Law No. 7150, which has not yet been adopted (at the time of the study). What exactly was the reason and what consequences this may have, we will try to establish by conducting a study in this paper. Methods: the research was based on the analysis of the legal framework of Ukraine, the European Union and other international acts, including those ratified by the Parliament of Ukraine. The research objective required an in-depth study of its individual components, for which the study is divided into a number of stages in order to form the necessary sequence of conclusions. The methodological basis of the study includes a combination of philosophical, general scientific and special legal methods of scientific knowledge. The study was conducted using the system of methods of scientific cognition. Results: the first version (and based on our research, we are almost certain that there will be subsequent versions) of the Law of Ukraine "On Virtual Assets", which was adopted on 15.03.2022, was an indicator that in the future Ukrainian companies and international investors will be able to operate legally in Ukraine. However, at this stage, the Law of Ukraine "On Virtual Assets" is still more declarative in nature. And it will unleash its potential only after it is brought in line with the MiCA regulations, and after the creation and approval of bylaws. Discussion: significant events have taken place since February 17, 2022, namely since the adoption of Law 2074 by the Parliament of Ukraine and until the beginning of 2023. Among such influential events is the fact that on June 23, 2022, Ukraine became a candidate for membership in the European Union. At the same time, the European Union has significantly updated the Crypto Asset Market Regulation (MiCA). Therefore, the domestic legislation regulating virtual assets needs to be revised due to the implementation of the MiCA.